From Corpora to Experiments: Methodological Triangulation in the Study of Word Order at the Interfaces in Adult Late Bilinguals (L2 learners) - Mendikoetxea, Amaya; Lozano, Cristóbal (Journal of psycholinguistic research, 2018)
This paper shows the need to triangulate different approaches in Bilingualism and Second Language Acquisition (SLA) research to fully understand late bilinguals’ interlanguage grammars. Methodologically, we show how experimental and corpus data can be (and should be) triangulated by reporting on a corpus study (Lozano and Mendikoetxea in Biling Lang Cognit 13(4):475–497, 2010 ) and a new follow-up offline experiment investigating Subject–Verb inversion (Subject–Verb/Verb–Subject order) in L1 Spanish–L2 English (n = 417). Theoretically, we follow a recent line in psycholinguistic approaches to Bilingualism and SLA research (Interface Hypothesis, Sorace in Linguist Approaches Biling 1(1):1–33, 2011 ). It focuses on the interface between syntax and language-external modules of the mind/brain (syntax-discourse [end-focus principle] and syntax-phonology [end-weight principle]) as well as a language-internal interface (lexicon-syntax [unaccusative hypothesis]). We argue that it is precisely this multi-faceted interface approach (corpus and experimental data, core syntax and the interfaces, representational and processing models) that provides a deeper understanding of (i) the factors that favour inversion in L2 acquisition in particular and (ii) interlanguage grammars in general.